Possible Synergy between Recombinant Factor VIIa and Prothrombin Complex Concentrate in Hemophilia Therapy - Key, Nigel S.; Christie, Beverly; Henderson, Nicole; Nelsestuen, Gary L. (Thrombosis and Haemostasis, 2002)
Recombinant factor VIIa (rFVIIa; Novoseven™) is used for treatment of hemophilia patients with inhibitors. There are poorly defined differences in clinical responsiveness between individuals. Prior to licensure in the United States, rFVIIa was available through the compassionate use program, during which two patients described in this study demonstrated an excellent response. More recently, one of these individuals showed a sub-optimal response to rFVIIa. One possible explanation for different treatment outcomes was sequential therapy with prothrombin complex concentrates (PCC) followed by rFVIIa in the compassionate use program. In support of this, an in vitro test showed that this patient had an exceptionally strong response to rFVIIa when it was added to whole blood after the patient received PCC therapy. Results with other patients supported this hypothesis. With further evaluation, a therapeutic approach combining sequential PCC and rFVIIa may prove useful for treatment of bleeding refractory to either agent used alone.
Keywords: Factor VIIa; prothrombin complex concentrates; haemophilia